All-Americans: Knute Rockne and the No-Glitz Man Who Tended His Flame - Christy Davis (Symphony in the Flint Hills, 2019)
Introduction: On March 31, 1931, a star fell from the sky above a remote Kansas pasture and changed the course of history. President Herbert Hoover called the plane crash a “national loss.” And perhaps more importantly to some, cowboy humorist Will Rogers called one of the fallen “a national hero.”